STRESS RESPONSES OF THREE SPECIES OF CYPRINID: COMMON CARP (Cyprinus carpio), BONYLIP BARB (Osteochilus hasselty), AND TORSORO (Tor soro) SUBJECTED TO OXYGEN DEPLETION - Wahyulia Cahyanti; Nunak Nafiqoh; Otong Zenal Arifin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Fish in stressed conditions will show symptoms of a decreased physiological function. These symptoms include changes in the respiration system (gills, breathing frequency) and blood hemoglobin. Cyprinid fish are active fish that require high oxygen levels. In a minimum oxygen condition, cyprinid fish are easy to get stressed. Despite the extensive literature on cyprinid biology, comparison of declined physiological functions due to oxygen depletion in cyprinid are few and far between. The purpose of this study was to determine the physiological reactions and organ responses of three species of Cyprinidae, common carp (Cyprinus carpio), nilem carp (Osteochilus hasselti), and Torsoro carp (Tor soro) challenged to oxygen depletion. The study was conducted using 18 fishes for each species with an average body weight of 48.11 ± 4.24 g. Oxygen depletion challenge was done by placing the test fish in closed and non-aerated aquaria (40 cm x 20 cm x 20 cm). The dissolved oxygen level in each aquarium was measured every 30 minutes. Fish breathing frequency was calculated by the frequencies of mouth movement every 30 minutes. Histological examination of gills and blood was taken from healthy fish (at the beginning of treatment) and at LC50 (lethal concentration). The results showed that oxygen depletion reduced blood hemoglobin levels down to 5.1 ± 1.4 gram%, 3.3 ± 1.15 gram%, and 1.5 ± 0.71 gram% for goldfish, nilem, and torsoro, respectively. The respiratory rate varied from normal to depleted conditions. When depletion occurred, the respiratory rate increased and decreased again when the fish started to get weak. In normal conditions, the breathing frequency of goldfish was 60 beats/minute, nilem was 108 ± 20.8 beats/minute, and Tor soro was 144 ± 31.7 beats/minute. The highest respiration frequency occurred in tor soro fish in the 150th minute with a value of 216 ± 0.0 beats/minute. The fastest mortality at LC50% occurred in torsoro at 245.00 ± 17.32 minutes.